2017
DOI: 10.1038/ngeo3013
|View full text |Cite
|
Sign up to set email alerts
|

The strength of the meridional overturning circulation of the stratosphere

Abstract: The distribution of gases such as ozone and water vapour in the stratosphere — which affect surface climate — is influenced by the meridional overturning of mass in the stratosphere, the Brewer–Dobson circulation. However, observation-based estimates of its global strength are difficult to obtain. Here we present two calculations of the mean strength of the meridional overturning of the stratosphere. We analyze satellite data that document the global diabatic circulation between 2007– 2011, and compare these t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
53
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(58 citation statements)
references
References 49 publications
(60 reference statements)
5
53
0
Order By: Relevance
“…However, the difference between the CO 2 and SF 6 ages obtained in this study is so large that the "polar vortex mixing" effect is not a major factor. Linz et al (2017) compared the MIPAS SF 6 age with the N 2 O age calculated from the N 2 O data from the Global OZone Chemistry And Related trace gas Data records for the Stratosphere (GOZCARDS) and showed that the MIPAS SF 6 age is larger than the N 2 O age in the tropics. The CO 2 and SF 6 ages observed in this study are consistent with the N 2 O age rather than the MIPAS SF 6 age, although the observation period is different.…”
Section: Difference In the Co 2 And Sf 6 Agesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the difference between the CO 2 and SF 6 ages obtained in this study is so large that the "polar vortex mixing" effect is not a major factor. Linz et al (2017) compared the MIPAS SF 6 age with the N 2 O age calculated from the N 2 O data from the Global OZone Chemistry And Related trace gas Data records for the Stratosphere (GOZCARDS) and showed that the MIPAS SF 6 age is larger than the N 2 O age in the tropics. The CO 2 and SF 6 ages observed in this study are consistent with the N 2 O age rather than the MIPAS SF 6 age, although the observation period is different.…”
Section: Difference In the Co 2 And Sf 6 Agesmentioning
confidence: 99%
“…From an analysis of the ERA-Interim dataset, Diallo et al (2012) also showed a negative trend over the 1989-2010 period in the lower stratosphere below 25 km. Linz et al (2017) discussed the strength of the meridional overturning circulation of the stratosphere by using satellite observation data of SF 6 and N 2 O and suggested that a mesospheric SF 6 loss is important for age estimation using SF 6 mole fraction in the upper layer.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, AoA determined from GOZCARDS N 2 O data is used (gray circles) (Andrews et al, 2001;Linz et al, 2017). The latitudinal AoA distribution is shown together with AoA from MIPAS SF 6 data (gray diamond symbols), with AoA from GOZCARDS N 2 O data (gray circle) and with in situ measurements of Andrews et al (2001) (black cross for CO 2 and black dot for SF 6 ).…”
Section: Tropical Upwellingmentioning
confidence: 99%
“…[a] in situ data we also use AoA calculated from the satellitebased GOZCARDS (Global OZone Chemistry And Related trace gas Data records for the Stratosphere, Froidevaux et al, 2015) N 2 O data, using the empirical relationship of N 2 O with AoA (see Andrews et al, 2001;Linz et al, 2017) (2001) were not reported with uncertainties. Moreover, AoA determined from GOZCARDS N 2 O data is used (gray circles) (Andrews et al, 2001;Linz et al, 2017).…”
Section: Tropical Upwellingmentioning
confidence: 99%
“…The difference in the estimated time lag between CO 2 and SF 6 was also reported by previous studies (e.g., Andrew et al 2001;Sugawara et al 2017), however, the cause is not yet understood well. The downward transport of the mesospheric air with low SF 6 mole fractions is suggested as one of possible candidates (e.g., Reddmann et al 2001;Linz et al 2017). …”
Section: Methodsmentioning
confidence: 99%